2017
DOI: 10.11607/prd.3274
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Periodontal Assessment of 137 Teeth After Featheredge Preparation and Gingittage

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…In summary, as previously discussed, periodontal health appears compatible with a range of values for EP 151 and when a featheredge finish line design is adopted 93,197,203,205–208 …”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…In summary, as previously discussed, periodontal health appears compatible with a range of values for EP 151 and when a featheredge finish line design is adopted 93,197,203,205–208 …”
Section: Resultsmentioning
confidence: 55%
“…Gingival margin changes have been associated with fixed prosthodontic procedures 80,81,83–90 . They can be linked to a variety of factors, including crown preparation and margin position, 80,91–93 gingival displacement and impressions, 81,84,94 provisional prostheses, 95 and luting agents 96…”
Section: Resultsmentioning
confidence: 99%
“…These are important findings as, according to the literature, the risk of gingivitis is always slightly greater around prosthetic crowns on horizontal dental finish lines, where GI values are usually seen to increase [35][36][37][38]. It should be noted that several previous studies have reported bleeding on probing [6,28,39], a parameter that the present study omitted since periodontal conditions were evaluated by means of the GI.…”
Section: Discussionmentioning
confidence: 59%
“…Gingival thickness has not been a parameter that is commonly reported in previous articles. Nevertheless, some studies record the patient's gingival biotype, although changes over time have not been reported [6,16]. In the work by Paniz, neither preparation protocols nor provisionalization were described correctly, and changes in several variables were not monitored over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation